Proyecto de factibilidad para la implementación de una lavadora automática de ropa en la parroquia Guayzimi, cantón Nangaritza, provincia de Zamora Chinchipe. - CUEVA ZHIÑIN, VERONICA ELIZABETH (2012)
Whereas clause that the parish Guayzimi, cantonal head of the canton Nangaritza, county of Zamora Chinchipe is part of the domestic South, it is an important area, it has a population of 2.598 inhabitants, for the development of the project one works with the segment families and to generate ideas of business that you/they will go in benefit of the place contributing social and economically to the parish, given its little production index. The objective of the investigative work is to determine the feasibility for the creation of a company of Laundry and Automatic Drying of Clothes in the parish Guayzimi, for what was of supreme importance to carry out an analysis and the market study, same that allows to know or to estimate the existent demand, to execute the project. For the development of the investigation it was used the materials, methods, technical and procedures, the materials that were used are: computer, flash memory, pens, impressions, calculator, etc. the Scientific method: it establishes relationships among the facts raised in the parish Guayzimi of the problem in the laundry of traditional clothes and the form that are carried out the activities for the development of the project, Deductive: for the Theoretical Marco's development; Inductive: for the bid and ask determination; Descriptive: to explain the process of the service; Historical: gather the historical records of the parish with respect to the existence of dedicated companies to the benefit of this class of services. As part of the work he/she also took into account the techniques as the Observation and Survey giving to know that in the town companies that offer the service of automatic laundry of clothes don't exist and a representative sample of 242 surveys applied to the families of the parish settled down, he/she will also allow to have a clear concept of the fact or phenomenon for the process of the system of the service. The Study of Market - It leaves essential of the project where quantitative and qualitative information of the topic is obtained to be developed by means of the application of surveys and interviews for that which is justified this work. The Technical Study - It allows to establish the good size of the project, by means of the dear installed capacity of 109.500 annual services and an utilized capacity of 34,19% with the one that will be taking place 37.440 annual services and a market share of 61,89%, this company will locate it to him in the parish Guayzimi, in the streets Av. Monsignor Jorge Mosquera and February 17. The company of service has an Organizational Structure that completes a fundamental paper in the execution of the project, for what is important and necessary to emphasize that the participation of each member of the company is key for the service. For the implementation of the present project a total investment is needed of $9.877,00 having a financing characteristic of 39,25 equivalent% to $3.877,00, and an external of 60,75% that ascends yearly at $6.000,00 financed by the National Bank of Development in its line of business credits with an interest rate of 12%. The price for kilo for the laundry and automatic drying of clothes is of $0, 91 cents of dollar; also, it was considered the prices of the competition. In the Financial Evaluation he/she was proven that the project is feasible due to the positive financial indicators that it generates the project in the Net present value (they GO), the value is of $20.786,22 dollars, the Internal Rate of Return (TIR) of the investment of the project it is 79,73%, giving a Relationship Benefits Cost (RBC) of 0,35 cents for each overturned dollar, the Period of Recovery of Capital (PRC) it will be in the 1 year-old time, 7 months and 24 days. The project supports an increment of 13,02% in the costs and a decrease of 9,98% in the revenues. Finally realized all the pertinent studies with the obtained results, it is deduced that the project is feasible of carrying out, since its demand, direct inputs and existent manpower assure an acceptable economic yield for the investors and the opportunity of creating working sources and with it to contribute to the socioeconomic development of the parish.